Inclusive Local Irregularity Vertex Coloring In Grid Graph Family - Kristiana, Arika Indah; Agatha, Alvian Bagus; Hussen, Saddam; Prihandini, Rafiantika Megahnia; Alfarisi, Ridho; Siddiqui, M. Kamran (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
Let  is a simple graph and connected where  is vertex set and  is edge set. A maping  as vertex k- labeling and function :  is inclusive local irregularity vertex coloring, with . The minimum number of colors produced from inclusive local irregularity vertex coloring of graph  is called inclusive chromatic number local irregularity, denoted by . On this paper, we learn about the inclusive local irregularity vertex coloring and determine the chromatic number on grid graph family.